2009
DOI: 10.1104/pp.109.146514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rubisco Activase Deficiency on the Temperature Response of CO2 Assimilation Rate and Rubisco Activation State: Insights from Transgenic Tobacco with Reduced Amounts of Rubisco Activase    

Abstract: The activation of Rubisco in vivo requires the presence of the regulatory protein Rubisco activase. To elucidate its role in maintaining CO 2 assimilation rate at high temperature, we examined the temperature response of CO 2 assimilation rate at 380 mL L 21 CO 2 concentration (A 380 ) and Rubisco activation state in wild-type and transgenic tobacco (Nicotiana tabacum) with reduced Rubisco activase content grown at either 20°C or 30°C. Analyses of gas exchange and chlorophyll fluorescence showed that in the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 54 publications
(89 reference statements)
3
63
1
1
Order By: Relevance
“…At higher temperature, the steady-state photosynthesis in rice can be influenced by Rubisco activase. Yamori and von Cammerer (2009) reported that steady-state photosynthetic rate at higher temperature decreased in transgenic tobacco containing reduced Rubisco activase, which exhibited the same levels of photosynthesis as the wild-type at growth temperature. Since Rubisco activase limitation on photosynthesis may vary with the rice cultivar, it can be physiologically meaningful and also useful for improvement of photosynthetic efficiency in rice to analyze the difference in the potential of light-induction and heat tolerance of photosynthesis induced by Rubisco activase among various cultivars and wild relatives.…”
Section: Discussionmentioning
confidence: 99%
“…At higher temperature, the steady-state photosynthesis in rice can be influenced by Rubisco activase. Yamori and von Cammerer (2009) reported that steady-state photosynthetic rate at higher temperature decreased in transgenic tobacco containing reduced Rubisco activase, which exhibited the same levels of photosynthesis as the wild-type at growth temperature. Since Rubisco activase limitation on photosynthesis may vary with the rice cultivar, it can be physiologically meaningful and also useful for improvement of photosynthetic efficiency in rice to analyze the difference in the potential of light-induction and heat tolerance of photosynthesis induced by Rubisco activase among various cultivars and wild relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen leaf sample was ground in liquid nitrogen and homogenized in an extraction buffer (Yamori and von Caemmerer, 2009;Yamori et al, 2010a). The content of Rieske FeS of Cyt b 6 /f complex and d-subunit of ATP synthase was quantified by immunoblotting with anti-Rieske FeS antibody and anti-ATP synthase (d) antibody (Agrisera).…”
Section: Gas Exchange and Fluorescence Measurementsmentioning
confidence: 99%
“…After gas exchange had reached the steady-state rate for at least 30 min at a given leaf temperature, the leaf section in the chamber was taken out and immediately frozen in liquid nitrogen. Rubisco catalytic sites and Rubisco activation state were determined by the stoichiometric binding of 14 C-carboxy-arabinitol-P 2 , whereas chloroplast NADP-MDH activation state was assayed by monitoring NADH oxidation at 340 nm (Yamori and von Caemmerer, 2009). …”
Section: Gas Exchange and Fluorescence Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low rubisco activity at 25 • C might be due to the reduction in RuBP regeneration [7,25]. RuBP regeneration might be affected by the lower RuBP consumption by rubisco.…”
Section: Discussionmentioning
confidence: 99%